The Influence of the Project Based Learning Model on Interest in Learning Student Class V Social Sciences Content KKG Cluster 3 Bunga Karang District Sombori Island Regency Morowali - Darwis; Misnah; Mahfud M Gamar (Kirana Publisher (KNPub), 2024)
Field education become Foundation for development something nation . Enhancement quality education is the most strategic thing in increase quality Human Resources ( HR ) to have knowledge , attitudes and skills oriented towards mastery​ knowledge knowledge and technology . Formulation problem application of the Project Based Learning learning model , interest Study students in social studies learning in class V, influence use of the Project Based Learning learning model towards interest Study student . Research purposes Analyze influence use of the Project Based Learning learning model towards interest Study student . Types of research This is quantitative . Study quantitative can interpreted as method Research based on philosophy​ positivism , used For research on populations or sample certain . Research methods experiment is method Research conducted​ with experiment , which is used For know influence variable independent ( treatment ) towards variable dependent ( result ) in controlled conditions .​ Research results Observation results teacher activities , known that teacher activities in application based teaching materials project based learning is obtained mark all encompassing​ activity beginning , core, and conclusion that is accomplished , with thereby implementation of the learning process show success teacher activities included carry out steps learningd with Good.